Literary and Arts Sciences - Montero Zayas, Geovannys; Jarmoch, Edward; Maturkanič, Patrik; Paľa, Gabriel; Kondrla, Peter (Journal of Education Culture and Society, 2024)
Aim. The article aims to offer a theoretical approach to the literary sciences and art, in essential aspects such as their general theoretical and methodological assumptions, the relations with other sciences, and the functions performed by the literary sciences and art in the system of culture.Methods. The research methods used were the inductive-deductive and the analytical-synthetic.Results. As a result, a theoretical article is presented which reveals essential issues of the literary sciences and art, from the processing of a wide literature and historical, theoretical and critical sources associated with literature and different artistic manifestations.Conclusion. The literary and art sciences make up a complex and diverse field of knowledge, which offers transcendental knowledge in the approaches to these expressions of culture. The literary and art sciences fulfill several functions in the system of culture, given fundamentally by the spiritual needs they satisfy, oriented towards the subjectivity of cultural subjects and projected towards the survival of culture. These functions change in human cultural communities, and often determine the existence and trends in the development of literary sciences and art.Cognitive value. The article reveals essential issues to the literary sciences and art, so it is an indispensable source in the approaches to a theory of these forms of human knowledge.